Barry Lopez’s relational Arctic - Kjeldaas, Sigfrid (Universidad de Alcalá, 2014)
"Arctic dreams: imagination and desire in a Northern landscape"(1986) can be read as American nature writer Barry Lopez’s attempt to evoke a more profound and ecologically sound understanding of the North American Arctic. This article investigates how Arctic Dreams uses insights from Jacob von Uexküll’s Umwelt theory, in combination with what Tim Ingold describes as a particular form of animism associated with circumpolar indigenous hunter cultures, to portray the Arctic natural environment as a living and lively space. Doreen Massey has described such spaces as recognizing plurality and allowing encounters. By highlighting networks of relationship and trajectories both human (historical) and animal (evolutionary), Arctic Dreams recognizes human and animal cultures that not only exist upon and can lay claim to this land, but that in a fundamental way is the land. In this way the text dismisses previous conceptions of the North-American Arctic as an empty space awaiting colonization and modernization, while on a deeper level it also questions the modern nature/culture dichotomy that allows nature to be perceived as the mere substratum of culture. El libro "Arctic dreams: imagination and desire in a Northern landscape" (1986) puede considerarse un intento por parte del escritor de la naturaleza americano Barry Lopez de evocar un conocimiento más profundo y ecológicamente sensato del Ártico norteamericano. Este artículo analiza cómo Arctic Dreams utiliza la teoría Umwelt de Jacob von Uexküll, combinada con lo que Tim Ingold describe como una forma particular de animismo asociada con las culturas de los indígenas cazadores circumpolares, para retratar el entorno natural ártico como un lugar vivo y vivaz. Doreen Massey ha descrito dichos lugares como capaces de reconocer la pluralidad y permitir encuentros. Al destacar las redes de relaciones y de trayectorias tanto humanas (históricas) como de animales (evolucionarias), Arctic Dreams reconoce culturas humanas y animales que no sólo existen sobre y puede reclamar ...